Levamisole Ameliorates Rheumatoid Arthritis by Downregulating the PI3K/Akt Pathway in SD Rats - Mu Guo; Xiangbin Yu; Zesheng Yang; Hanlu Zheng; Jiahui Zhang; Junxiang Wang; Yiqi Liao; Weirui Huang; Zhaolong Lin; Yingxue Yan; Nengfu Qiu; Jianmin Chen; et al. (MDPI AG, 2024)
Background/Objectives: Rheumatoid arthritis (RA) is a systemic chronic autoimmune disease characterized by a protracted course, high rates of morbidity, and disability yet lacks effective therapeutic modalities. Levamisole (LVM), an immunomodulatory drug, has been clinically reported for its potential in RA treatment, while its therapeutic mechanism toward RA remains to be elucidated. Hence, this study provides theoretical support for the application of LVM in the treatment of RA. Methods: This study employed male Sprague-Dawley (SD) rats to construct the adjuvant-induced arthritis (AIA) model, administering LVM orally (5 mg/kg, 15 mg/kg, and 45 mg/kg) for 25 days. An evaluation of LVM's therapeutic effects on RA was conducted through arthritis index scores, paw pad thickness, paw volume, hematoxylin and eosin (H&E) staining, 3D microcomputed tomography (micro-CT) scans, serum levels of pro-/anti-inflammatory cytokines, and serum biochemical indicators. Western blotting and immunohistochemistry staining were utilized to measure the expression levels of phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) proteins in synovial and ankle joint tissues. Results: Treatment with the median dose of LVM (15 mg/kg, M-LVM) significantly reduced the arthritis index (p < 0.01), paw pad thickness (p < 0.001), and paw volume (p < 0.01) without affecting body weight. Additionally, M-LVM alleviated inflammatory lesions in the synovium and ankle joints and also normalized serum levels of interleukin-1 beta (IL-1β), tumor necrosis factor-alpha (TNF-α), and transforming growth factor-beta (TGF-β). The Model group exhibited significant increases in serum levels of alkaline phosphatase (ALP) (p < 0.01), creatine kinase (CK) (p < 0.05), and glucose (GLU) (p < 0.001) compared with the Control group; however, M-LVM effectively regulated these parameters to normal levels. Western blotting and immunohistochemistry staining revealed that PI3K-/Akt-related proteins were highly expressed in the synovial and ankle joint tissues of rats in the Model group, while treatment with M-LVM significantly reduced the expression of these proteins. Furthermore, histological examination of major organs (heart, liver, lungs, kidneys, and thymus) showed no significant pathological changes, with the exception of the spleen, where M-LVM ameliorated splenic lesions. Conclusions: We demonstrate that LVM at an optimal dose substantially relieves synovitis and bone erosion in AIA rats by inhibiting the PI3K/Akt signaling pathway.